Mengenal Perilaku Pengendara Kendaraan Dalam Upaya Mencegah Terjadinya Kecelakaan Di Jalan Raya - (Jurusan Teknik Sipil Politeknik Negeri Semarang), Nur Setiaji Pamungkas (Teknis, 2014)
Traffic accidents on the road is an event that is unexpected and unintended , involving a vehicle with or without other road users , resulting in loss of life or loss of property (PP 43/93 Section 93). Traffic accidents can be: 1) the victim died (fatal), 2) severe injuries (serious injury), and 3) minor injuries (slight injury). The occurrence of road traffic accidents in urban areas can be identified there are several main factors are: human (driver, pedestrian), vehicle, road and environment. Conditions for each category of causes of traffic accidents on the road is different. Knowledge of the characteristics of the three factors causing the accident is required in an attempt to decrease the rate of occurrence of accidents on the highway. Pamungkas, NS, in his writings mentions that most of the accidents on the highway Surabaya-Gempol caused by human factors (63.09 %). The vehicle factors accounted for 28.33 %, while road and environmental factors accounted for 8.58 %. Knowledge of the behavior of motorists who need to be understood to include the characteristics of the drive, sensing, and perception and reaction.Â Keywords : accident, characteristics, sensing, perception and reaction